Emotional Dynamics and Regulation Strategies in EFL Writing Classrooms - Ariyanti, Ariyanti; Amat, Rafidah; Nimasari, Elok Putri (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
Recent research in second language acquisition has shown that learners’ emotional dynamics such as anxiety, enjoyment, and frustration, and their use of emotion regulation strategies significantly influence engagement and performance in EFL writing classrooms. Thus, the current research aims at investigating EFL students’ emotional dynamics and the emotion regulation strategies they apply when completing their writing tasks. This is a phenomenological study in which six university students were given an open-ended questionnaire. Subsequently, the data were analysed using a thematic analysis technique until the data were formed into themes and a conceptual framework illustrating the types of emotional dynamics they faced and what strategies of emotion regulation they commonly applied during the process of writing. The novel finding revealed after building themes was from the up and down or emotional fluctuation, e.g., anxious to enjoyment, fear to relax, shaped the students to have a mental of resilience as a learner. Finally, the pedagogical implications of the research were explained further.